O princípio da verdade material no processo tributário - Macei, Demetrius Nichele (2012)
The present work aims to identify the meaning and scope of the Principle of Material Truth in Taxation Procedure. Start by drawing a picture of truth, since his philosophical point of view, covering the works of consensus on the subject to finish the chapter with the importance of Truth to the law, especially in the tax proceeding. Discusses the approach points of the Criminal Law, Civil Law and Tax Law for the attainment of truth in the process, especially through use of the Institute of proof. Then deals the Tax Procedure Law and the Brazilian Legal System, through the identification of the legal relationship between the tax authorities and the taxpayer in its dimensions static, dynamic and critical. It focuses on the critical dimension in the study of the relationship, dealing with the general principles governing the procedure in tax matters, administrative and judicial spheres. Finally, it examines the role and position of the judge's jurisprudence on the subject. The conclusion reveals the need unrestricted application of the Principle of Material Truth in tax procedural law, especially in the sphere of the judicial process